KONSEP ASD (ANTICIPATE SMOG DISASTER) - Saputra, Nuzul Ramadhan; Susanto, Pendi; Nuushana, Emhas (Program Kreativitas Mahasiswa - Gagasan Tertulis, 2014)
From June 2013 to March 2014, the smog intensity in Indonesia increased. The smog came from Kalimantan and Sumatra islands. This was happened because of the increase of the forest fire in order to open the new farmland in those two islands. The impact of this forest fire was the increasing of the smog in the two islands, even it spread until Singapore and Malaysia. Based on the issue, the writers want to give solution through ASD (Anticipate Smog Disaster). The concept of ASD (Anticipate Smog Disaster) is a solution- and is a visionary alternative for the safety of the people in the country and also abroad that causes by the rapidly declining air quality in some areas due to smog from land or forest fires. The purpose of this concept is to decrease the smog intensity around 50%-60%, so the ISPA rate will decrease. It will recover the land, water, and air transportation as well as maintain the bilateral relationship with our neighbor countries. The ASD concept provides zero burning program, limited the land opening permission, land patrol, creating the new methods of providing the new land and providing the simple agricultural tools for traditional farmers. Strategic steps to implement this concept: raise the support from the government, survey the field condition, survey the society, socialization to head of village or respect people in community, community socialization, implement the concept with the society. We expect this concept can decrease the intensity of smog, so it will not spread to Singapore and Malaysia. In the end, the quality of the air is kept in the good condition.Keywords: Smog Disaster, Bilateral, ISPA